(untitled) (Bangladesh Agronomy Journal, 2021)
Four lentil genotypes/varieties BLX-010014-9, ILI-5143, BARI Mosur-3 and BARI Mosur-2 were given irrigation regimes (with and without irrigation) to evaluate the physiological indices of genotypes against drought stress. The experiment was conducted during rabi (winter) season of 2017-18 under pot culture at the Plant Physiology Division of Bangladesh Agricultural Research Institute (BARI). The experimental design was randomized completed block (RCBD) with six replications. Irrespective of genotypes/varieties, physiological parameters as well as seed yield were greatly affected due to irrigation regimes. Based on physiological parameters like accumulation of chlorophyll, enzymatic and non-enzymatic antioxidantthe genotype BLX-010014-9 was found to be drought tolerant due to its higher and lower values of enzymatic and non-enzymatic antioxidant indices (greater CAT, POD, APX and lower MDA) across the irrigation levels treatment. This genotype may be further explored to characterize its genes and mechanisms against drought stress for increased lentil production and way to developing the drought tolerant variety/varieties. Bangladesh Agron. J. 2020, 23(2): 97-102